CURRENT PRINCIPLES OF TREATMENT AND PREVENTION OF SYNOVITIS BY THE CASE OF GONARTHRITIS - Могила, О.О. (World of Medicine and Biology, 2017)
The incidence of synovitis in recent years has been steadily increasing, ranging from 9 to 33% among the various manifestations of chronic knee joint diseases. In the international practice of treating synovitis of the knee joint, conservative treatment is usually carried out. The most popular methods are arthroscopy with biopsy of the synovial membrane and synovial fluid, surgical methods are used: synovectomy of the knee joint, synovecapsulotomy and arthroplasty of the knee joint. These methods have several disadvantages, namely the trauma of the intervention itself, which causes the intensity of postoperative pain syndrome and adversely affects the development of joint movements and requires hospitalization of the patient. Our studies show that synovitis of the knee joint can be effectively cured out-patient, especially with primary and secondary synovitis. The proposed method of treatment and prevention of synovitis of the knee joint is based on the fact that the cause of its occurrence is the development of tendonitis of the muscles of the Semi group (semimembranous, semitendinous, tender and tailor muscle). That is why the treatment should be phased and begin with the treatment of tendinitis (or bezeksudativnogo synovitis of the semimembranous muscle), which is always present with synovitis. The task of this method of treatment of synovitis of knee joints is the phased medication use of drugs depending on the nature of the disease course of this pathology, which ensures an increase in the effectiveness of treatment, reduction of pain and prevention of synovitis.